Acupuncture for posttonsillectomy pain in children: a randomized, controlled study. Issue 6 (7th February 2015) - Gilbey, Peter; Bretler, Shlomi; Avraham, Yaniv; Sharabi‐Nov, Adi; Ibrgimov, Sasha; Luder, Anthony; Cravero, Joseph
Summary Background Surgeons have searched for the technique or medication that will produce a 'painless tonsillectomy'; however, this seems to be an impossible goal. Previous studies have shown that perioperative acupuncture may be a useful adjunct for acute postoperative pain and that acupuncture, in addition to nonsteroidal anti‐inflammatory drugs, is effective in adults for the treatment of postoperative swallowing pain after tonsillectomy. Acupuncture has been shown to be safe in children. A retrospective review of acupuncture for posttonsillectomy pain in juvenile patients showed a significantly reduced pain score immediately after treatment. Aim To examine whether acupuncture, in addition to conventional analgesic treatment, will be effective in the treatment of posttonsillectomy pain in children. Methods We conducted a randomized, controlled, single‐blinded study comparing conventional postoperative analgesic treatment with the same regime plus acupuncture to assess whether postoperative treatment of children aged 3–12 years undergoing tonsillectomy with acupuncture will reduce pain and to examine possible unwanted effects of this treatment. Results Sixty children were recruited and randomly divided into a study group and a control group. The results indicate that in the study group, there was less pain, less analgesic drug consumption, and higher patient/parent satisfaction with analgesic treatment scores. No adverse effects were recorded. Conclusions Acupuncture, in addition to conventional analgesic treatment, is an effective treatment for posttonsillectomy pain. Acupuncture is safe and well received by children and their parents.